The role of dark matter annihilation in the radio emission of the galaxy cluster A520. Issue 2 (6th December 2018) - Marchegiani, P; Colafrancesco, S; Khanye, N F
ABSTRACT: A520 is a hot and luminous galaxy cluster, where gravitational lensing and X-ray measures reveal a different spatial distribution of baryonic and dark matter. This cluster hosts a radio halo, whose map shows a separation between the north-east and the south-west part of the cluster, similarly to what is observed in gravitational lensing maps. In this paper we study the possibility that the diffuse radio emission in this cluster is produced by dark matter annihilation. We find that in the whole cluster the radio emission should be dominated by baryonic phenomena; if a contribution from dark matter is present, it should be searched in a region in the NE part of the cluster, where a peak of the radio emission is located close to a dark matter subhalo, in a region where the X-ray emission is not very strong. By estimating the radio spectrum integrated in this region using data from publicly available surveys, we find that this spectrum can be reproduced by a dark matter model for a neutralino with mass 43 GeV and annihilation final state $b \bar{b}$ for a magnetic field of 5 $μ$ G.